ACTIVITIES OF BIOMASS/FIBEX CRUISE OF THE UMITAKA MARU (Collected Abstracts of Transactions of the Tokyo University of Fisheries No. 5,March 1982) - MURANO, Masaaki; INOUE, Kiyoshi (1982)
P(論文) departmental bulletin paper